Long-term control of HIV-1 in hemophiliacs carrying slow-progressing allele HLA-B*5101. - Kawashima, Y; Kuse, N; Gatanaga, H; Naruto, T; Fujiwara, M; Dohki, S; Akahoshi, T; Maenaka, K; Goulder, P; Oka, S; Takiguchi, M (2010)
HLA-B*51 alleles are reported to be associated with slow disease progression to AIDS, but the mechanism underlying this association is still unclear. In the present study, we analyzed the effect of HLA-B*5101 on clinical outcome for Japanese hemophiliacs who had been infected with HIV-1 before 1985 and had been recruited in 1998 for this study. HLA-B*5101(+) hemophiliacs exhibited significantly slow progression. The analysis of HLA-B*5101-restricted HIV-1-specific cytotoxic T-lymphocyte (CTL) responses to 4 HLA-B*-restricted epitopes in 10 antiretroviral-therapy (ART)-free HLA-B*5101(+) hemophiliacs showed that the frequency of Pol283-8-specific CD8(+) T cells was inversely correlated with the viral load, whereas the frequencies of CD8(+) T cells specific for 3 other epitopes were positively correlated with the viral load. The HLA-B*5101(+) hemophiliacs whose HIV-1 replication had been controlled for approximately 25 years had HIV-1 possessing the wild-type Pol283-8 sequence or the Pol283-8V mutant, which does not critically affect T-cell recognition, whereas other HLA-B*5101(+) hemophiliacs had HIV-1 with escape mutations in this epitope. The results suggest that the control of HIV-1 over approximately 25 years in HLA-B*5101-positive hemophiliacs is associated with a Pol283-8-specific CD8(+) T-cell response and that lack of control of HIV-1 is associated with the appearance of Pol283-8-specific escape mutants.